Advanced stage mucinous epithelial ovarian cancer: The Hellenic Cooperative Oncology Group experience - Pectasides, D.; Fountzilas, G.; Aravantinos, G.; Kalofonos, H.P.; Efstathiou, E.; Salamalekis, E.; Farmakis, D.; Skarlos, D.; Briasoulis, E.; Economopoulos, T.; Dimopoulos, M.A. (Gynecologic Oncology, 2005)
Objective. Mucinous epithelial ovarian cancer (mEOC) representing about 10% of all EOC are known to be possibly resistant to platinum-based chemotherapy and bear a poorer prognosis with respect to other subtypes of EOC. This study was undertaken to compare response and survival to platinum-based chemotherapy between patients with advanced stages III and IV mEOC and serous EOC (sEOC). Methods. A retrospective analysis was performed in 47 patients with advanced stage of mEOC treated with first-line platinum-based chemotherapy in the context of several study protocols of the Hellenic Cooperative Oncology Group (HeCOG) between 6/7/1983 and 25/2/2003. The outcome was compared to that of 94 patients with sEOC treated with the same protocols during the same study period (ratio mucinous: serous 1:2). Results. One hundred forty-one patients (47 stages III and IV mEOC, 94 stages III and IV sEOC) treated with platinum-based chemotherapy were analyzed. The overall response rate for mEOC was 38.5% (complete remission 18%) (95% CI 23.4-55.4%) and 70% (complete remission 47%) (95% CI 58.5-80.3%) for sEOC (P = 0.001). After a median follow-up of 77.8 months, median survival and time to tumor progression (TTP) were not significantly different between the two groups (33.2 months [95% CI 23.3-43.1 months] vs. 38.0 months [95% CI 26.8-49.2 months], P = 0.46, 11.8 months [95% CI 7.2-16.4 months] vs. 20.0 months [95% CI 15.7-24.2 months], P = 0.18, respectively). Conclusion. Patients with mEOC have significantly lower response to first-line platinum-based chemotherapy compared to patients with sEOC. This low response to platinum-based chemotherapy was not translated in inferior TTP or survival. Our data indicate that a new strategy for chemotherapy in mEOC should be adopted, one that focuses on new agents without cross-resistance to platinum agents. © 2005 Elsevier Inc. All rights reserved.
Keywords: Mucinous epithelial ovarian cancer; Platinum-based chemotherapy; Response; Survival